Vectorial Formalism of Polyphase Synchronous Machine With Permanents Magnets - Abdelkrim Sellam; Boubakeur Dehiba; Mohamed B. Benabdallah; Mohamed Abid; Nacéra Bachir Bouiadjra; Boubakeur Bensaid; Mustapha Djouhri (Aceh International Journal of Science and Technology, 2013)
Abstract- This paper presents a mathematical model that transforms the real machine to fictitious machines and our goal is to simulate these and see the behavior of these machines in load. The polyphase machines are developed mainly in the field of variable speed drives of high power because increasing the number of phases on the one hand allows to reduce the dimensions of the components in power modulators energy and secondly to improve the operating safety. By a vector approach (vector space), it is possible to find a set of single-phase machine and / or two-phase fictitious equivalent to polyphase synchronous machine. These fictitious machines are coupled electrically and mechanically but decoupled magnetically. This approach leads to introduce the concept of the equivalent machine (multimachine multiconverter system MMS) which aims to analyze systems composed of multiple machines (or multiple converters) in electric drives. A first classification multimachine multiconverter system follows naturally from MMS formalism. We present an example of a pentaphase (polyphase) synchronous machine for a simulation and study the behavior of the machine load. Keywords: Polyphase machines, multimachine concept, vector space, eigenvectors, eigenvalues, pentaphase machine.